1997
DOI: 10.1002/(sici)1097-4636(19971215)37:4<585::aid-jbm18>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling study of adsorption of poly-L-lysine onto silica glass

Abstract: A research program was initiated with both experimental and computational chemistry based molecular modeling components to investigate specific amino acid-surface interactions. The experimental portion of this study, with details reported elsewhere, investigated the adsorption of selected molecular weights of poly(L-lysine) onto silica glass microspheres with the adsorption enthalpy per adsorbed mer determined to be -0.23 +/- 0.13 kcal/mol (mean +/- 95% confidence interval). Molecular modeling of this system w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…Molecular modeling is a powerful tool that can enable the complex processes of protein adsorption on a submolecular level to be addressed. The theoretical study presented herein builds on previously reported modeling and experimental studies by Latour and coworkers,40–42 which address the thermodynamic contributions of the adsorption of mid‐chain peptide residues to synthetic surfaces. Currently, experimental studies are being conducted in attempt to verify the findings of this present study.…”
Section: Resultsmentioning
confidence: 96%
“…Molecular modeling is a powerful tool that can enable the complex processes of protein adsorption on a submolecular level to be addressed. The theoretical study presented herein builds on previously reported modeling and experimental studies by Latour and coworkers,40–42 which address the thermodynamic contributions of the adsorption of mid‐chain peptide residues to synthetic surfaces. Currently, experimental studies are being conducted in attempt to verify the findings of this present study.…”
Section: Resultsmentioning
confidence: 96%
“…35 Poly-L-lysine (PLL) is a versatile polymer, composed of positively charged lysine amino acid as a repeat unit, which has attractive biochemical properties, including hydrophilicity, excellent biocompatibility and an acceptable degree of biodegradability. Because PLL is positively charged at physiological pH, it can be easily adsorbed on a large variety of negatively charged substrates via electrostatic interactions, including glass, 36 metals, 37 polymers, 38 and metallic oxides. 39 Furthermore, PLL polymers can be easily modified with nonionic side-chains (like PEG/OEG), thereby making it an ideal candidate for engineering biomaterial interfaces, such as surface coatings, 37,40 drug, 41 gene, 42 and protein 43 delivery platforms, and hydrogel scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…The affinity of a ligand for its receptor can also be evaluated by means of semiempirical QM methods,7–11 such as AM112 or PM3,13 which allow the physico‐chemical properties of medium‐sized and large systems to be investigated with a reasonable computational cost. In spite of the known limitations of semiempirical methods based on the neglect diatomic differential overlap (NDDO) approximation,14–16 they continue to find use in different applications such as the prediction of specific surface interactions on silica17 or carbon nanotubes,18 the qualitative interpretation of ligand‐protein19 interactions, and the estimation of the solvation contribution20 in those kinds of interactions. One of the problems associated with NDDO‐based methods is that they do not reproduce hydrogen bonding with good accuracy.…”
Section: Introductionmentioning
confidence: 99%